UJI EFEKTIVITAS ANTIBIOTIK EKSTRAK DAUN BELIMBING WULUH (AVERRHOA BILIMBI L.) DAN EKSTRAK HABATUSSAUDA (NIGELLA SATIVA L.) TERHADAP PENYEMBUHAN LUKA SAYAT MENCIT JANTAN (MUS MUSCULUS L.) YANG TERINFEKSI STAPHYLOCOCCUS AUREUS SECARA IN VIVO - SARAH RAISAH ZEIN HARAHAP; YENITA . (LP2MTBM MAKARIOZ, 2021)
Each person will experience several types of infections, one of which is a skin infection caused by the bacteriumStaphylococcus aureus, because this bacterium is the main pathogen for humans. Excessive use of antibiotics in thetreatment of infections can cause bacterial resistance because the uncontrolled us of antibiotics will increase resistance tobacteria that were previously sensitive.Starfruit leaves (Averrhoa bilimbi L.) contain flavonoid and triterpenoid compositionsthat can cure the special bacterial disease Staphylococcus aureus available on skin. Besides starfruit (Averrhoa bilimbi L.)can also use habatussdauda (Nigella sativa L.) which contains bioactive thymoquinone, oleic acid, linoleic acid and saponinsto enhance the body immune system and anti-inflammator. To determine the effectiveness of antibiotic extract of starfruit leafextract (Averrhoa bilimbi L.) with habatussauda extract (Nigella sativa L.) on wound healing in male mice (Mus musculus L.)infected with Staphylococcus aureus. Experimental research with Pre-test and Post test design with Control Group Designmethod. Starfruit leaf extract (Averrhoa bilimbi L.) with the lowest dose can reduce the length of the wound significantlycompared to habatussauda (Nigella sativa L.) extract. Starfruit leaf extract (Averrhoa bilimbi L.) with a dose of 200mg/kgBB/day more effectively can heal the length of the cut.